Peace and Region Semester, a strategy for comprehensive university training and contribution to regional development (2025)
Service-Learning (S-L) is a pedagogical strategy employed by Higher Education Institutions (HEIs) to promote the comprehensive and relevant education of their students, as well as to facilitate the social outreach of these institutions in their geographical area of influence. An example of the implementation of this strategy is the Peace and Region Semester (PRS) at the University of Ibagué, located in the Tolima region of Colombia. The results of the impact analysis generated by the PRS on a pilot group of 105 students who participated in the PRS during the 2023A period, using various statistical techniques, suggest that this pedagogical strategy does contribute to the comprehensive education of students and serves as a pathway for the university to make an effective contribution to regional development